Terapia combinada com eritropoetina e fator estimulante da colônia de granulócitos em um modelo de infarto agudo do miocárdio - Angeli, Franca Stedile (2012)
Background: Erythropoietin (EPO) and granulocyte colony stimulating factor (GCSF) have generated interest as novel therapies after myocardial infarction (MI), but the effect of combination therapy has not been studied in the large animal model.Objetives: We investigated the impact of prolonged combination therapy with EPO and GCSF on cardiac function, infarct size, and vascular density after MI in a porcine model.Methods: MI was induced in pigs by a 90 min balloon occlusion of the left anterior descending coronary artery. 16 animals were treated with EPO+GCSF, or saline (control group). Cardiac function was assessed by echocardiography and pressure-volume measurements at baseline, 1 and 6 weeks post-MI. Histopathology was performed 6 weeks post-MI.Results: At week 6, EPO+GCSF therapy stabilized left ventricular ejection fraction, (41±1% vs. 33±1%, p<0.01) and improved diastolic function compared to the control group. Histopathology revealed increased areas of viable myocardium and vascular density in the EPO+GCSF therapy, compared to the control. Despite these encouraging results, in a historical analysis comparing combination therapy with monotherapy with EPO or GCSF, there were no significant additive benefits in the LVEF and volumes overtime using the combination therapy.Conclusion: Our findings indicate that EPO+GCSF combination therapy promotes stabilization of cardiac function after acute MI. However, combination therapy does not seem to be superior to monotherapy with either EPO or GCSF